AHP Method for Determining the Right Teaching Method for Mathematics Subjects: Metode Ahp untuk Menentukan Metode Pengajaran yang Tepat Pada Mata Pelajaran Matematika - Wulan Andang; Raimon Efendi (Perkumpulan Doktor Indonesia Maju (PDIM), 2021)
This research was conducted to study and implement methods of AHP as a decision support to determine the proper method of teaching mathematics (case study in SMPN 1 Koto Baru). The problems encountered in the process of learning mathematics is the number of students who think mathematics is the most difficult that they feel afraid and reluctant to learn. Many criteria in determining the method of teaching. The method used is the Analytic Hierarchy Process (AHP). AHP method requires input data including alternative assessment criteria and the data processed using AHP calculations and using Super Decisions software. The result is the value of the weight of each alternative are ranked from highest to lowest. The result value has been ranked teaching methods can be used as a decision support in determining the proper method of teaching math